Taḥlīlu al Akhṭā’i fī Nuṭqi al Lughati al ‘Arabiyyati ‘inda al Talāmīżi fī Ma’hadi al Nūri Tangkit Sungai Gelam Muaro Jāmbī (Dirāsatun Taḥlīliyyatun fī ‘Ilmi al Aṣwāti) - Syari, Anitha Purnama; Mahendra, Ahdiyat (Al-Uslub: Journal of Arabic Linguistic and Literature, 2022)
This study aims to determine the forms of errors in Arabic pronunciation at the An-Nur Tangkit Islamic Boarding School, Sungai Gelam Muaro Jambi at the phonological level, the factors of errors in Arabic pronunciation. The type of research used is qualitative research. Collecting data from this study using the methods of observation, interviews, and documentation. The results of this study indicate that the forms of Arabic pronunciation errors that occur in Pondok Pesantren An-Nur Tangkit Sungai Gelam Muaro Jambi are grouped into 2: 1. Phoneme changes using thin sounds are replaced with thick sounds or vice versa. on the contrary. 2. The letters are similar in pronunciation, but where they come out differently.The factors of errors in Arabic pronunciation are students find it difficult to concentrate while studying, inadequate facilities and infrastructure, the assumption that Arabic language lessons are difficult lessons, mother tongue and environmental factors. The solution made by the teacher is to create fun lessons, pay special attention to students who are lacking in Arabic pronunciation, prepare their own facilities and infrastructure that are not yet available at school.